2017
DOI: 10.1177/1076029617727858
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Paradox in Patients With Deep Venous Thrombosis

Abstract: We aimed to investigate the association between obesity and deep venous thrombosis (DVT) in a country with a high prevalence of obesity. This is a retrospective cohort study of patients who presented with DVT between 2008 and 2012. Data were analyzed and compared based on body mass index (BMI), and patients were classified into normal (<25), overweight (25 to <30), obese I (30 to <35), obese II (35 to <40), and obese III (40). Among 662 patients with DVT, 28% were overweight and 49% were obese. The mean age wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 35 publications
2
24
2
Order By: Relevance
“…A large cohort study in the Middle East showed that obesity is associated with venous thrombosis [ 32 ]. In addition, obesity is associated with cancer, diabetes, cardiovascular disease, hypercholesterolemia, and other chronic diseases [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large cohort study in the Middle East showed that obesity is associated with venous thrombosis [ 32 ]. In addition, obesity is associated with cancer, diabetes, cardiovascular disease, hypercholesterolemia, and other chronic diseases [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies[ 34 , 35 ] have reported that diabetes is a risk factor for DVT. Orthopedic surgery patients are in a state of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Kornblith et al [23] demonstrated obesity independently contributed to hypercoagulability after injury. Additionally, the functional exercise and activity in obese patients were less than that of non-obese patients, which increases the pressure of venous valve and the risk of hemodynamic abnormalities [24]. Furthermore, obesity demonstrated to be associated with more surgical duration, intraoperative blood loss, postoperative infection, and even mortality [25].…”
Section: Discussionmentioning
confidence: 99%